Peran Perawat Dalam Edukasi Dan Skrining Kanker Payudara Di Indonesia - Martha Sutriska Sagala; Rustianna Tumanggor (STIKES Columbia Asia Medan, 2025)
Breast cancer remains a major cause of cancer-related mortality among women in Indonesia, with late detection being a major contributing factor. Nurses play a critical role in promoting early detection through education and clinical screening. This literature review aims to examine the role of nurses in breast cancer education and screening in Indonesia. A total of 25 relevant articles published between 2019 and 2024 were reviewed from national and international journals. The results show that nurse-led education significantly improves knowledge and practice of breast self-examination (BSE), while nurse involvement in clinical breast examination (CBE) contributes to early detection. However, barriers such as limited training, lack of resources, and insufficient institutional support hinder optimal implementation. The study highlights the importance of strengthening nurse capacity and integrating community-based education models to improve early breast cancer detection in Indonesia. This review provides a theoretical and practical foundation for strengthening the role of nurses in national cancer control strategies.